2007
DOI: 10.1002/pssa.200622559
|View full text |Cite
|
Sign up to set email alerts
|

Exactness of simplified scalar optical approaches in modelling a threshold operation of possible nitride vertical‐cavity surface‐emitting diode lasers

Abstract: Modern small‐size vertical‐cavity surface‐emitting diode lasers (VCSELs) require principally fully vectorial optical modelling because their cavity sizes are of the order of the wavelength of emitted radiation. However, much simpler scalar approaches are often surprisingly exact even beyond the limits of their confirmed validity. Therefore, in the present paper, reasonable limits of an application of simplified scalar optical approaches (instead of more exact but also much more involved and time‐consuming rigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…where k = nk 0 = nω c 0 was used, where n is the (real part of) the refractive index of the material inz = 0, and γ = −2n ′′ ω c 0 , where n ′′ is the imaginary part of the refractive index. Evidently, the last term in (12) is responsible for the standing wave effect, depending on the phase relation ∆ϕ between the counterpropagating fields. In a material without gain/loss, n ′′ = 0, so the power flux can then be viewed as being composed of independent contributions from the right and left propagating field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…where k = nk 0 = nω c 0 was used, where n is the (real part of) the refractive index of the material inz = 0, and γ = −2n ′′ ω c 0 , where n ′′ is the imaginary part of the refractive index. Evidently, the last term in (12) is responsible for the standing wave effect, depending on the phase relation ∆ϕ between the counterpropagating fields. In a material without gain/loss, n ′′ = 0, so the power flux can then be viewed as being composed of independent contributions from the right and left propagating field.…”
Section: Discussionmentioning
confidence: 99%
“…The scalar method is almost identical with our 2D method, and is based on the effective index or effective frequency method [14], which assumes a moderate refractive index contrast so that the optical field is separable in the spatial coordinates in such a way that the wave equation can be reduced to a pair of almost one-dimensional equations. It is shown in [12,13] that the simplified scalar method and the rigorous vectorial method agree remarkably well in cases where diffraction losses are negligible. The vectorial method is very similar to our 3D method in the consideration of the structure and the cavity field.…”
Section: Numerical Simulation Methods and Loss Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…The latter is directly associated with a radial profile of the threshold current density injected into the VCSEL active region (Figure 7), becoming in these double intracavity contacted VCSELs more and more nonuniform with increasing active-region radius r A [25,26]. Therefore, for larger r A it is found that higher-order transverse modes become the lowest-threshold modes, which limits the desired Guassian mode operation to relatively small active region diameter.…”
Section: Simulation Of Oxide-confined Vcselsmentioning
confidence: 99%
“…The structure and parameters used in the simulations are described in [26]. Our self-consistent simulation model is used to determine possible room-temperature CW performance characteristics of GaN-based VCSELs.…”
Section: Comparison Of Self-consistent Models Assuming Scalar and Vecmentioning
confidence: 99%